Comprehensive comparison on the anti-inflammation and GC-MS-based metabolomics discrimination between Bupleuri chinense DC. and B. scorzonerifolium Willd - Zhao, Mingming; Xiao, Linxuan; Linghu, Ke-Gang; Zhao, Guanding; Chen, Qiling; Shen, Liyu; Dar, Parsa; Chen, Meiwan; Hu, Yuan; Zhang, Jinming; Yu, Hua (Frontiers in Pharmacology, 2022)
Bupleuri Radix (BR) is a traditional Chinese medicine and widely used for cold and fever, influenza, inflammation, hepatitis and menstrual diseases. Two authentic medicinal plants of Bupleuri chinense DC. (Beichaihu, BCH) and B. scorzonerifolium Willd. (Nanchiahu, NCH) are recommended by the current Chinese Pharmacopoeia for BR. In the present study, the comparative investigations on the anti-inflammatory effects and gas chromatography-mass spectrometry (GC-MS)-based metabolomics for the species discrimination of BCH and NCH were conducted and reported. The in vitro evaluations indicated that the supercritical fluid extracts (SFEs) (IC50 of 6.39±0.52 and .32±0.05 mg(herb)/mL for BCH and NCH) were determined to be more potent than those of the hydro-distillation extracts (HDEs) (IC50 of 203.90±8.08 and 32.32±2.27 mg(herb)/mL for BCH and NCH) against LPS-induced inflammation in RAW264.7 macrophages. The higher anti-inflammatory effects of NCH were associated to its different chemical compositions to the BCH as characterized by the GC-MS analysis. Furthermore, based on the metabolomics and deep chemometric approaches, a minimum combination containing 15 chemical markers was optimized from the identified components and successfully applied for the species discrimination of BCH and NCH. This study not only helps to comparative understand BCH and NCH both in phytochemistry and pharmacology, but also provides the potential chemical markers for improvement of methods for the quality control of BCH and NCH.